PENGARUH DUKUNGAN ORGANISASI DAN PERSEPSI KEADILAN ORGANISASIONAL TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI : STUDI PADA KARYAWAN BEACUKAI PEKANBARU - Defrionaldo Defrionaldo; Harif Amali Rivai (Departemen Manajemen, 2019)
This writing provides the studies about performance which OCB mediated. This research observes the impacts of organization support, organizational justice perception towards Beacukai employees’ performance in Pekanbaru. The population consists of seventy five (75) persons Beacukai employees in Pekanbaru. The processing of the obtained data was done using the SPSS software Version 22 for Windows and SmartPLS software. The results of this research suggests that organizational support have not significant negative effect on the performance and not mediated by OCB,organizational support have a positive significant on the OCB, organizational justice perception have a positive significant on the performance and employees’s OCB, OCB have a positive significant on the performance, and OCB mediate a part of organizational justice perception on the performance. The implication for the office is that the better the implementation of organizational support, improvement of justice perception, it will increase employees performance and appear the OCB